Evaluation of a novel fluorescent nanobeacon for targeted imaging of Thomsen-Friedenreich associated colorectal cancer - Nakase H (Dove Medical Press, 2017)
Hiroshi Nakase,1,2 Shinji Sakuma,3 Takumi Fukuchi,4 Takuya Yoshino,1,5 Kohta Mohri,3 Kohei Miyata,3,6 Hironori Kumagai,6 Ken-Ichiro Hiwatari,6 Kazufumi Tsubaki,6 Tetsuya Ikejima,6 Etsuo Tobita,6 Meiying Zhu,7 Kevin J Wilson,7 Kay Washington,8 John C Gore,7,9–13 Wellington Pham7,9–12,14 1Division of Endoscopy, Kyoto University Hospital, Kyoto, Japan; 2Department of Gastroenterology and Hepatology, Sapporo Medical University School of Medicine, Sapporo, Hokkaido, Japan; 3Faculty of Pharmaceutical Sciences, Setsunan University, Hirakata, Osaka, Japan; 4Gastroenterology and Hepatology, Osakafu Saiseikai Nakatsu Hospital, Osaka, Japan; 5Division of Inflammatory Bowel Disease, Digestive Disease Center, Kitano Hospital, Osaka, Japan; 6Advanced Materials R&D Laboratory, ADEKA Corp., Tokyo, Japan; 7Department of Radiology, Vanderbilt University Institute of Imaging Science, 8Division of Gastrointestinal and Hepatic Pathology, Vanderbilt School of Medicine, 9Department of Radiology and Radiological Sciences, 10Department of Biomedical Engineering, 11Vanderbilt Ingram Cancer Center, Vanderbilt School of Medicine, 12Vanderbilt Brain Institute, 13Molecular Physiology and Biophysics, 14Vanderbilt Institute of Chemical Biology, Vanderbilt University, Nashville, TN, USA Abstract: The Thomsen–Friedenreich (TF) antigen represents a prognostic biomarker of colorectal carcinoma. Here, using a nanobeacon, the surface of which was fabricated with peanut agglutinin as TF-binding molecules, we demonstrate that the nanobeacon is able to detect TF antigen in frozen and freshly biopsied polyps using fluorescence microscopy. Our results provide important clues about how to detect aberrant colonic tissues in the most timely fashion. Given the versatile application method for this topical nanobeacon, the protocol used in this work is amenable to clinical colonoscopy. Moreover, the prospects of clinical translation of this technology are evident. Keywords: TF antigen, fluorescence colonoscopy, nanobeacon, colorectal cancer